Effectiveness of Levateracetam in Patients with Brain Tumors (Medical Forum Monthly, 2023)
Objective: The present study aimed to assess the effectiveness of levateracetam in brain tumor’s patients.Study Design: A retrospective studyPlace and Duration of Study: This study was conducted at the Neurosurgery, Mardan Medical Complex, Mardan from 16th April 2018 to 15th May 2023.Materials and Methods: Patients diagnosed of brain tumors and placement on LEV were enrolled. All the patients with concomitant epileptic conditions were excluded. The frequency of seizure was calculated for each individual. The seizure frequency significant improvement was referred to seizure activity reduction (>50%) against pre-LEV baseline. Age, initial tumor location, gender, and treatment methods were also obtained for each patient.Results: Of the total patients, there were 54 (55.1%) male and 44 (44.9%) females. The overall mean age was 48.62±12.86 years with an age range 20 to 80 years. Out of 98 BT patients, the incidence of partial seizure and generalized seizures was 84 (85.7%) and 14 (14.3%) respectively. Of the total, levetiracetam was administrated in 82 (83.7%) patients due to epilepsy diagnosis. Upon the final diagnosis, about 87.8% (n=72) patients taken levetiracetam were recovered and seizure free; due to intolerable adverse effects, 3 (3.7%) patients were withdrawn. There were no laboratory anomalies seen in subjects receiving concurrent treatment.Conclusion: The present trial confirmed that levetiracetam is both effective and safe in brain tumor patients. As a result, brain tumor causing epileptic seizures can be treated with levetiracetam as a preferred or standard treatment.